Tobacco use as a risk indicator for periodontal disease in a sample of Northwestern Ontario residents / by Ann Marie Chlebovec. - Chlebovec, Ann Marie (My University, 2006)
According to Pairo and Neill (2002), tobacco use has been identified as a significant risk factor in the development and progression of periodontal disease. However, throughout the literature the effects of smoking on individual variables such as bleeding on probing, amounts of plaque and calculus, probing depth, attachment loss and recession are fraught with controversy and ambiguity. The purpose of the present study was to determine the influence of tobacco use on the periodontal health status of Northwestern Ontario residents. Specifically, clinical features of periodontal disease in adults in relation to smoking behaviours were measured. The study will contribute new information about the risk of tobacco use and oral hygiene practices. It is anticipated that this study may be useful to dental professionals, researchers and local health promoters who are challenged with the responsibility of educating people about the negative consequences of tobacco use and the importance of maintaining appropriate oral hygiene practices. Statement of Problem • To determine a measure of prevalence of periodontal disease in an urban community in Northwestern Ontario • To determine the likelihood of periodontal disease between tobacco users and nonusers • To determine the oral hygiene practices between tobacco users and non-users • To determine the level of periodontal disease in tobacco users versus non-tobacco users Method One-hundred adult patients were recruited over a six-month period from a dental clinic in Thunder Bay, Ontario. Participants completed a survey while waiting for their routine dental appointment. The questionnaire was designed to determine tobacco use: frequency, type, duration and quantity. Moreover, the questionnaire was used to collect information about oral hygiene practices, age and gender, and general health. All patients had undergone a clinical and radiographic assessment by the dentist and hygienist. The periodontal status was based on the following clinical measures: gingival bleeding tendency, level of gingival inflammation, levels of bacterial plaque and calculus, periodontal pocket depth, clinical attachment loss, and number of teeth retained. Results and Conclusion Tobacco use is a causal mechanism of periodontal disease. The results obtained in this study support previous research, which demonstrated that smokers are at greater risk of developing severe periodontal disease than non-smokers. Odds ratios reported in the present study indicated that tobacco users are twice as likely to show severe periodontal disease. Furthermore, the present study also demonstrated that tobacco users were more than twice as likely to demonstrate higher levels of plaque and both supragingival and subgingival calculus, which are noted precursors of gingivalin flammation leading to periodontal disease. While these findings are important alone, the study also showed that self-reported oral hygiene behaviours were not significantly different between smokers and non-smokers, suggesting that despite the best intentions of smokers to self maintain good oral health through subscribing to regular dental visits and practices, periodontal disease and its related sequelae continue to develop. Study participants from Thunder Bay Region, Northwestern Ontario.
Keywords: Periodontal disease; Periodontal disease - Etiology; Periodontal disease - Risk factors; Northwestern Ontario; Tobacco use and periodontal health